2016
DOI: 10.1002/ajh.24312
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutically targeting SELF‐reinforcing leukemic niches in acute myeloid leukemia: A worthy endeavor?

Abstract: A tight relationship between the acute myeloid leukemia (AML) population and the bone marrow (BM) microenvironment has been convincingly established. The AML clone contains leukemic stem cells (LSCs) that compete with normal hematopoietic stem cells (HSCs) for niche occupancy and remodel the niche; whereas, the BM microenvironment might promote AML development and progression not only through hypoxia and homing/adhesion molecules, but also through genetic defects. Although it is still unknown whether the niche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 144 publications
(167 reference statements)
0
17
0
Order By: Relevance
“…Besides the direct impact of activated Notch signaling on LSC and HSC, the augmented proliferation and infiltration of LSC compared to normal HSC could be favorable for their competition for the niche over HSC. Various studies have demonstrated that LSC could positively remodel the BM microenvironment to enhance support of LSC at the expense of HSC, 47 , 48 and this remodeling may in turn further promote leukemia progression and impair normal hematopoiesis. In addition, the reduced expression of Cxcl12 , Scf and Angpt1 in Twist1 -deleted mice may also account for the opposing impact of Twist1 deletion on HSC and LSC, since compared with HSC, LSC are less factor-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the direct impact of activated Notch signaling on LSC and HSC, the augmented proliferation and infiltration of LSC compared to normal HSC could be favorable for their competition for the niche over HSC. Various studies have demonstrated that LSC could positively remodel the BM microenvironment to enhance support of LSC at the expense of HSC, 47 , 48 and this remodeling may in turn further promote leukemia progression and impair normal hematopoiesis. In addition, the reduced expression of Cxcl12 , Scf and Angpt1 in Twist1 -deleted mice may also account for the opposing impact of Twist1 deletion on HSC and LSC, since compared with HSC, LSC are less factor-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to develop targeted therapies with clinical efficacy, it will be critical to identify unifying mechanisms required for AML progression, irrespective of the diverse genetic and molecular abnormalities. In vitro functional analyses have aided these drug discovery efforts (Tibes et al, 2012), but are commonly conducted in the absence of microenvironmental factors such as secreted cytokines and growth factors known to influence cell survival and response to therapy (Bernasconi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need for identification of new therapeutic targets and development of new therapeutic strategies that are more efficient and better tolerated [22]. Targeting of the bidirectional communication between AML cells and their neighboring leukemia-supporting stromal cells is a possible approach [23,24,25,26,27,28]. In a previous study investigating another patient cohort, we described that high constitutive mediator release is associated with better long-term overall survival compared with low constitutive release [29].…”
Section: Introductionmentioning
confidence: 99%